EVALUASI TEBAL PERKERASAN PADA RUNWAY BANDARA SYUKURAN AMINUDDIN AMIR LUWUK BERDASARKAN CUMULATIVE DAMAGE FAILURE - Hariyami, Diah; Setiawan, Arief; Arifin, Syamsul (FROPIL (Forum Profesional Teknik Sipil), 2023)
Air transportation is a mode of transportation still quite in demand, although recently there has been a decline in passengers. Syukur Aminuddin Amir Luwuk Airport belongs to the category of Class II Domestic Airport with airside facilities, a Runway with a size of 2,250 m x 45 m, a Taxiway 60 m x 18 m, and an Apron with a size of 315 x 15 m. The operation of several types of aircraft with a larger capacity occurs due to the increase in the number of passengers every year. An increase in the number of passengers will certainly have an impact on the number of aircraft movements, it is necessary to analyze how to determine the thickness of the runway pavement which is influenced by the type of aircraft that will operate based on the subgrade conditions that are there using the FAARFIELD method. The results of the evaluation on the thickness of the runway pavement which has a CBR value of 15%, with a pavement thickness of 215 mm for HMA Surface, 152 mm for Crushed Aggregate, and 200 mm for Uncrushed Aggregate with a service life of 20 years in 2040 it was found that the Subgrade CDF value was 0.00 and the HMA CDF of 0.86. The test results with FAARFIELD software change the pavement thickness for the base layer to 152 mm (minimum value) from the value of 100 mm. So planning the thickness of the pavement requires an additional layer of 52 mm.